Pelestarian dan Pengembangan Alat Musik Tiup Tkud pada Masyarakat Desa Dano Lamo Jambi - Rendi Surya Pamungkas; Kiswanto Kiswanto (YASIN, 2026)
Modernization and technological development have reduced the living space of traditional arts, including the wind instrument Tkud in the social life and musical traditions of the Dano Lamo Village community in Jambi. This study aimed to analyze the preservation and development of Tkud amid these dynamics of social change. A qualitative approach with an ethnographic method was employed to understand Tkud as a cultural practice in context through field observations, interviews with artists and customary leaders, and documentation. The findings indicate a shift in the function and contextual use of Tkud in the community’s social life, which has weakened traditional intergenerational transmission patterns. Preservation and development efforts have been carried out through strategies of innovation and adaptation, particularly by collaborating Tkud with modern musical instruments, which has contributed to expanding performance spaces, increasing the appeal of traditional arts, and opening opportunities for the regeneration of artists. Nevertheless, low interest among the younger generation due to the dominance of digital media remains a major challenge for sustaining the tradition. These findings affirm that Tkud as a traditional art form constitutes a dynamic and adaptive cultural practice, in which transformations of form and function serve as key strategies for preservation without eroding the local cultural identity of the Dano Lamo community.